Prototype implementation and experimental analysis of water heating using recovered waste heat of chimneys. (March 2015) - Khaled, Mahmoud; Ramadan, Mohamad; Chahine, Khaled; Assi, Ali
Abstract: This work discusses a waste heat recovery system (WHRS) applied to chimneys for heating water in residential buildings. A prototype illustrating the suggested system is implemented and tested. Different waste heat scenarios by varying the quantity of burned firewood (heat input) are experimented. The temperature at different parts of the WHRS and the gas flow rates of the exhaust pipes are measured. Measurements showed that the temperature of 95 L tank of water can be increased by 68 °C within one hour. Obtained results show that the convection and radiation exchanges at the bottom surface of the tank have a considerable impact on the total heat transfer rate of the water (as high as 70%).